The Effect of Leadership and Motivation on The Performance of High School Teachers in Metro City - M. Ihsan Dacholfany; Durotun Nasikah (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The purpose of this study was to determine the direct positive effect of leadership on performance, to determine the direct positive effect of motivation on performance and to determine the direct positive effect of leadership on motivation. In this study using a questionnaire questionnaire given to the respondents as many as 235 respondents. The questionnaire was scored using a Likert scale with a scale of 1 – 5. The results of this study were then analyzed using Structural Equation Modeling (SEM) using the LISREL program. The results of this study are that leadership has a direct positive effect on performance, motivation has a direct positive effect on performance and leadership has a direct positive effect on motivation.